(untitled) (REMUNOM, 2026)
Objectives: To gather and discuss the main instruments used to assess the food security status of the elderly. Methods: Searches were carried out in the Lilacs, Medline/PubMed, Scopus, Web of Science, Embase and Cochrane databases representing the grey literature. Results: 8,360 studies were found, of which 13 remained after the selection stages. Conclusion: The articles present diverse instruments to assess the food security of the elderly, with adaptations to different cultures and contexts. However, despite being validated, some instruments used to assess the food security status of the elderly may not include characteristics of the senescence process. Furthermore, if inadequately designed in relation to the elderly, they expose them to fatigue, emotional discomfort and unreliable results.